Design of Android, PHP (Condeigniter) and MySQL-Based Franchise Information System - Nur Subchan (Program Pendidikan Vokasi Universitas Brawijaya, 2014)
The development of technology today has a lot of information systems that are constructed in real time and online which allows one to access them from anywhere and get the latest information. Competition in different business sectors is supported by the rapid development of information technology. The need of information for good stocks becomes a necessity for the management team that needs the help of appropriate information technology, appropriate distribution of information, and prompt customer service. The design of this system uses Codeigniter, MySQL database and PHP as the programming language. By making use of this system, management team can control the stalls in handling the transaction, determine the stock of goods in each stall precisely, transform the excessive goods and the lack ones in other stalls, supply the needs of goods in stalls according to customers’ needs, and obtain transaction reports in every stall precisely.